The Use of Freshwater Sapropel in Agricultural Production: A New Frontier in Kenya - Sylvia I. Murunga; Eliud N. Wafula; Joseph Sang (Advances in Agriculture)
Opportunities for sustainable agriculture development in Kenya which heavily depends on healthy soil and soil microbial diversity can be found in the promotion of organic farming. The increasing populations, higher demands for animal and plant products, climate change impacts, and weather conditions necessitate novel ideas and technologies to try reverse the adverse effects of excessive use of inorganic fertilizers and to maximize the potential of the land. Sapropel, a promising biological deposit from freshwater lakes, has found its limelight in its use in agricultural crop production as a soil conditioner and biofertilizer. This could be an ultimate practice for sustainable food and energy production in Kenya. This review aims at presenting information in the literature about the potential use of the organic fertilizer based on sapropels in intensified crop production and their main effects on plant growth. It discusses soil fertility, the composition of sapropels, and their application and advantages in agricultural production. It is evident from the review that sapropel can be considered as a resource that is valuable with wide application possibilities in agriculture. Sapropel can present an important contribution to the solution of the conservation of the fertility of the soil for integrated nutrient management systems to maintain agricultural productivity and help in environmental conservation.